A location-based application for public facility damage reporting in Manado City - Kenneth Palilingan; Salaki Reynaldo Joshua; Salvius Lengkong (Institute of Computer Science (IOCS), 2026)
This study presents the design and development of a Location Based Service (LBS)-based public facility damage reporting application for Manado City to address limitations in conventional public reporting mechanisms. The novelty of this research lies in the integration of real-time spatial reporting with the Rapid Application Development (RAD) method, enabling iterative and user-centered prototype development tailored to local government public service workflows. The RAD approach was implemented through iterative stages of requirement analysis, system design, prototyping, and evaluation involving user participation. The developed prototype enables users to submit damage reports with automatic GPS-based location detection, photographic evidence, and report status tracking. Functional evaluation using black box testing showed that all core user-side features operated successfully according to the defined requirements. Scenario-based testing involving six respondents indicated that report submission, location detection, and information display functions executed correctly under normal operating conditions. The results demonstrate that the proposed prototype improves the accuracy of reported locations and simplifies the public reporting process. Overall, this study highlights the potential of integrating LBS technology with the RAD approach to support responsive digital public service management and strengthen community participation in urban infrastructure monitoring within the local context of Manado City.